Analysis of the Influence of Work Ethos, Motivation and Organizational Commitment on Employee Performance of PT. Ratu Intan Kargo - Miswanul Arifin; Batubara, Soulthan Saladin; Darmilisani (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This research aims to analyze the influence of Work Motivation, Work Ethos, and Organizational Commitment on Employee Performance at PT. Queen Diamond Cargo. The research method used is a quantitative approach with descriptive and verification analysis, which includes multiple linear regression analysis, multiple correlation analysis, coefficient of determination, as well as the t test for partial testing and the F test for simultaneous testing. The sample used consisted of 50 employees taken using a saturated sampling technique. The research results show that: 1) Work Motivation has no significant effect on Employee Performance, with the calculated t value (1.071) being smaller than the t table (1.675) and a significance value of 0.290 (> 0.05). 2) Work Ethos has a positive and significant effect on Employee Performance, with the calculated t value (3.933) greater than the t table (1.675) and a significance value of 0.000 (< 0.05). 3) Organizational Commitment also has a positive and significant effect on Employee Performance, with the calculated t value (4.960) greater than the t table (1.675) and a significance value of 0.000 (< 0.05). 4) Simultaneously, Work Motivation, Work Ethos, and Organizational Commitment have a significant effect on Employee Performance, with the calculated F value (93.650) greater than the F table (2.366) and a significance value of 0.000 (< 0.05). These findings indicate that Work Ethos and Organizational Commitment play an important role in improving employee performance, while work motivation needs to be increased with a more appropriate approach in order to have a significant impact on performance.